Treatment of classical Hodgkin lymphoma in young adults aged 18–30 years with a modified paediatric Hodgkin lymphoma protocol. Results of a multicentre phase II clinical trial (CRUK/08/012). (11th November 2019) - Townsend, William; Leong, Sarah; Hoskin, Peter; Diez, Patricia; Patrick, Pip; Linch, David; Wong, Wai‐Lup; Kayani, Irfan; Sanghera, Bal; Lopes, Andre; Daw, Stephen; Collins, Graham; et al.
Summary: This phase II trial was designed to determine the safety and efficacy of a modified paediatric risk‐stratified protocol in young adults (18–30 years) with classical Hodgkin Lymphoma. The primary end‐point was neurotoxicity rate. The incidence of grade 3 neurotoxicity was 11% (80% CI, 5–19%); a true rate of neuropathy of >15% cannot be excluded. Neuropathy and associated deterioration in quality of life was largely reversible. The overall response rate was 100% with 40% complete remission (CR) rate. Twelve months disease‐free survival (DFS) was 91%. We demonstrate that a risk‐stratified paediatric combined modality treatment approach can be delivered to young adults without significant irreversible neuropathy.